Turkish memes and their users :|indexicality and identity through language play - Tunçer, Ümit Can. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
Internet memes have been a considerable point of interest to their users ever since their widespread recognition on social media channels. These digital items often come in different shapes and formats, varying from simple texts accompanying images to complex video edits and audiovisual tokens. Recently, memes have started to appear in linguistics studies (George, 2020; Vasquez and Aslan, 2021, Yus, 2020) where their text-over-image properties proved to be significant in terms of indexicality and identity construction, language play, and the pragmatics of incongruity resolutions. This thesis aims to contribute to what has been discussed in the literature, with a selection of additional language play strategies observed in memes and Caps in Turkish social media. In addition to these language play strategies, an analysis utilizing the Indexicality Framework (Eckert, 2008; Silverstein, 2003) was used to demonstrate the complex meaning-making processes of memes, as well as the identity construction via the use of text and imagery. The second part of this thesis involves a practice-oriented approach to the communities that make and consume memes on social media. For this part, the Community of Practice framework (Eckert and McConnell-Ginet, 1999; Meyerhoff and Strycharz, 2013; Wenger, 1998) was utilized to demonstrate how certain affordances of social media channels allow for different practices that form within the meme communities. Furthermore, the member practices were shown to demonstrate the membership and identity construction within the meme communities.
Keywords: Mimes -- turkey.